2016
DOI: 10.1080/02670844.2015.1108048
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray deposition of SnO2 films from precursor solution

Abstract: The electrospray deposition (ESD) of SnO 2 films from SnCl 4 .5H 2 O precursor solution was performed for gas sensor applications. Deposition time, solution flow rate and solution concentration were the main control parameters in the ESD process. The morphological properties of the deposited films were characterised by scanning electron microscopy. X-ray diffraction and energy dispersive X-ray analyses were employed to confirm the crystal phases and composition of the films. The best coatings with an island of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Another factor that influences surface morphology is the precursor liquid concentration. According to Gürbüz et al (2016), an increase in concentration increases the film thickness which affects morphology. In their study, they electrosprayed SnO2 precursor in ethanol (boiling point of 78 °C) for 1 h at a substrate temperature of 250 °C.…”
Section: Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor that influences surface morphology is the precursor liquid concentration. According to Gürbüz et al (2016), an increase in concentration increases the film thickness which affects morphology. In their study, they electrosprayed SnO2 precursor in ethanol (boiling point of 78 °C) for 1 h at a substrate temperature of 250 °C.…”
Section: Concentrationmentioning
confidence: 99%
“…With increasing time, the film thickens and the substrate surface is completely covered causing consecutive landing droplets to experience varying contact angles that alter the surface morphology. The effects of deposition time on surface morphology were investigated by Gürbüz et al (2016), who deposited 0.05 M SnO2 film from an ethanol precursor (boiling point of 78 °C) at a flow rate of 7.2 mL h −1 and at a substrate temperature of 250 °C for various time intervals. After 20 min, they observed that the substrate was sparsely covered because of the small number of deposited droplets.…”
Section: Deposition Timementioning
confidence: 99%
“…Another factor that influences surface morphology is the precursor liquid concentration. According to Gürbüz et al (2016), an increase in concentration increases the film thickness which affects morphology. In their study, they electrosprayed SnO2 precursor in ethanol (boiling point of 78 °C) at a substrate temperature of 250 °C for 1 h. Precursor concentrations were varied from 0.05 M to 0.2 M but flow rate was kept constant at 7.2 mL h −1 .…”
Section: Concentrationmentioning
confidence: 99%
“…This drawback has been addressed through multiplex ES (MES) techniques, demonstrating the simultaneous operation of hundreds of ES sources and a remarkable packing density exceeding 10 4 sources/cm 2 [33]. Thin films of MOS and conductive polymers have been prepared by ES of precursor solutions or nanoparticle suspensions for gas sensing applications [34][35][36][37][38][39]. Only recently ES has received attention for the preparation of gas sensors based on graphene [40,41].…”
Section: Introductionmentioning
confidence: 99%